The Impact of Tax Awareness, Literacy, and Sanctions on Taxpayer Compliance as an Effort to Improve the Regional Government Financial Management System - Yustina Alfira Nay; Ignatia Thomasita Bau Mau (STIE Amkop Makassar, 2025)
Researchers examined the impact of awareness, literacy, and tax sanctions on PKB compliance, a case study at the Lembata Samsat Office. Furthermore, this research does not only focus on tax compliance but is also directed as a strategic effort to improve the local government's financial management system. Optimizing revenue through increased taxpayer compliance is expected to strengthen regional fiscal capacity and support financial independence in accordance with the spirit of regional autonomy. The population in the study included all taxpayers registered at the Lembata Regency Samsat Office, reaching nearly 22,000 taxpayers. The results of the statistical analysis revealed that the awareness variable has a positive and significant effect on the level of taxpayer compliance. Meanwhile, unpaid literacy does not have a significant effect on the level of compliance. However, tax sanctions have a significant and positive effect on taxpayer compliance. Simultaneously, the three variables of awareness, literacy, and tax sanctions have a significant effect on motor vehicle taxpayer compliance. Therefore, local governments need to integrate these three aspects into regional fiscal policies through outreach programs, increasing the capacity of apparatus, and the use of transparent and easily accessible information technology. If implemented consistently, this approach can strengthen regional fiscal independence and support the achievement of transparent and sustainable financial governance throughout NTT.